2021
DOI: 10.3390/v13050758
|View full text |Cite
|
Sign up to set email alerts
|

D-Dimer Level and Neutrophils Count as Predictive and Prognostic Factors of Pulmonary Embolism in Severe Non-ICU COVID-19 Patients

Abstract: The incidence of pulmonary embolism (PE) is high during severe Coronavirus Disease 2019 (COVID-19). We aimed to identify predictive and prognostic factors of PE in non-ICU hospitalized COVID-19 patients. In the retrospective multicenter observational CLOTVID cohort, we enrolled patients with confirmed RT-PCR COVID-19 who were hospitalized in a medicine ward and also underwent a CT pulmonary angiography for a PE suspicion. Baseline data, laboratory biomarkers, treatments, and outcomes were collected. Predictive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…Concerning our study, we found that an even lower cut-off value for CRP (23 mg/L) is significantly associated with severe outcome (i.e., ICU admission). D-Dimers represent another well-established predictive factor in COVID-19, with generally accepted high-risk cut-offs ranging from 1 to 3 mg/L [ 31 , 32 ], values which are similar to the results (0.41–2.05) predicting a negative prognosis in patients included in our study.…”
Section: Discussionsupporting
confidence: 85%
“…Concerning our study, we found that an even lower cut-off value for CRP (23 mg/L) is significantly associated with severe outcome (i.e., ICU admission). D-Dimers represent another well-established predictive factor in COVID-19, with generally accepted high-risk cut-offs ranging from 1 to 3 mg/L [ 31 , 32 ], values which are similar to the results (0.41–2.05) predicting a negative prognosis in patients included in our study.…”
Section: Discussionsupporting
confidence: 85%
“…As confirmed by autopsy results, the elevated DD levels can be associated with fibrin deposits within pulmonary extravascular space and alveoli ( 67 ), but they may be non-specific to intravascular fibrin formation ( 87 ). High DD levels, together with elevated neutrophils, were reported to be predictive factors of pulmonary embolism in COVID-19 patients ( 88 ). DD and FIB levels are elevated in both COVID-19 and thromboembolism, and therefore as single tests are unspecific and unhelpful in the differentiation of these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…DD and FIB levels are elevated in both COVID-19 and thromboembolism, and therefore as single tests are unspecific and unhelpful in the differentiation of these conditions. In part, it may be explained by the involvement in abnormal coagulation in COVID-19 of different systems, including endothelial cells, complement activation, and hypofibrinolysis resulting in changes undetected by routine tests ( 39 , 88 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline D-dimers level above the upper limit of normal is associated with critical illness, thrombosis, acute kidney injury, and death [23] . In the CLOTVID cohort including non-ICU hospitalised patients, after adjustment of anticoagulant status and delay of follow-up, the combination of D-dimer level ≥2 µg/mL and neutrophils count ≥7.0 G/L on admission was associated with increased risk of death or ICU transfer [24] . The D-dimers level is related to thrombotic complications during COVID-19 but also the severity of the disease, especially the severity of lung injury.…”
Section: Methodsmentioning
confidence: 99%